THREE POOR JOBS: JEWISH, AMERICAN, AND HONG KONG - Chen, Chapman (POLISSEMA – Revista de Letras do ISCAP, 2019)
Objective: To find out how Ngo Loudou Hai Dongfui [My Father is Ash of the Party], a Hong Kong Cantonese rewriting of Neil Simon’s God’s Favorite, which is in turn an American rewriting of the Biblical story of Job, reflects the socio-political ideology of Hong Kong. Methodology: 1. Andre Lefevere (1992) argues that translation and adaptation are rewriting informed and influenced by the rewriter’s ideology. 2. Sirkku Aaltonen (2000) argues that whatever its self-proclaimed intentions, the selection of foreign plays is never an innocent decision, but rather a response to a wholly specific situation within one’s own culture and society. 3. In 2003, five to six years after the handover of Hong Kong from Britain to China, the Hong Kong government had proved itself to be grossly incompetent and the frustration of the Hong Kong citizens can be seen, for example, in one of the representative translated play performed there during the period, which originated from Neil Simon’s God’s Favorite. The religious theme of the former is turned political, and the time-space of the latter is changed from Long Island Sound in the 70s to Hong Kong in 1995.